AGAMA DAN TANTANGAN MODERNITAS - Munajah, Neneng (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2021)
Abstract (In English): Modern as a phase of life that is based on a rational pattern of thinking and lifestyle. Modern is rational, scientific, in accordance with the laws that apply in nature. As an understanding that applies science, there are consequences for absolute obligations and obligations for humans. Therefore, modernism is seen as God's commandment, thus Islam is synonymous with modernity. Modernism is an attempt to realize the truth, and that truth must be constantly sought. Truth, can only be achieved through a process, and humans will never get that truth perfectly, without real effort. An earnest search for truth is an attitude demanded by Islamic teachings. Modernism is the commandment of Islamic teachings, so Islam and modernity are identical. Rationalism is a paradigm based on the belief in the power of human reason and reason. In this paradigm, something is declared true, if it can be proven and can be accepted rationally. The phenomenon of scientism in the Western world shows us that science has become a new ideology or religion (pesudo religion). Western society marginalizes religion even if it can be said to abolish all sacred religious beliefs, and only accepts and believes in science. This belief emerged around the 18-19 century, science has become an idol that is worshiped by modern humans. Modernism is recognized to have brought wealth physically - materially. This phenomenon, becomes a tendency to dehumanize, is degraded, and reduces the quality of human life. Therefore, the noble values ​​of humanity, such as compassion, togetherness, solidarity and human brotherhood are not a concern, and what stands out from modern society is individualism. Humans in the modern age have become very vulnerable to disease, because they have actually lost one of the fundamental aspects, namely spiritualism. Modern man is hit by a spiritual void, he forgets the center of the circle of existence, namely, Allah SWT. Religion provides a solution to return to the center of the circle of human existence. Religion answers complex problems faced by humans, such as death, suffering and disaster. Religion answers the challenges of modernity, therefore religion must be a guide for human life who wants to achieve happiness in life both in this world and in the hereafter.